Modulation of Tim-3 Expression by Antigen-Dependent and -Independent Factors on T Cells from Patients with Chronic Hepatitis B Virus Infection - Dong, Jie; Yang, Xiao-Fei; Wang, Lin-Xu; Wei, Xin; Wang, An-Hui; Hao, Chun-Qiu; Shen, Huan-Jun; Huang, Chang-Xing; Zhang, Ye; Lian, Jian-Qi (Frontiers in Cellular and Infection Microbiology, 2017)
T-cell immunoglobulin domain and mucin domain-containing molecule-3 (Tim-3) was up-regulated on viral specific T cells and contributed to T cells exhaustion during chronic hepatitis B virus (HBV) infection. However, modulation of Tim-3 expression was still not fully elucidated. To evaluate the potential viral and inflammatory factors involved in the inductor of Tim-3 expression on T cells, 76 patients with chronic HBV infection (including 40 chronic hepatitis B [CHB] and 36 asymptomatic HBV carriers [AsC]) and 40 of normal controls (NCs) were enrolled in this study. Tim-3 expressions on CD4+ and CD8+ T cells were assessed in response to HBV-encoding antigens, HBV peptide pools, and common γ-chain (γc) cytokines stimulation by flow cytometry. HBV peptides and anti-CD3/CD28 directly induced Tim-3 expression on T cells. γc cytokines also drive Tim-3 up-regulations on both CD4+ and CD8+ T cells in patients with chronic HBV infection. However, γc cytokines did not enhance the Tim-3 inductions by either anti-CD3/CD28 or HBV peptides stimulation. Furthermore, γc cytokines-mediated Tim-3 induction could not be abrogated by γc cytokine receptor-neutralizing antibodies. The current results suggested that elevation of Tim-3 expression on T cells could be regulated by both antigen-dependent and -independent manner in patients with chronic HBV infection. The role of γc cytokines in modulation of inhibitory pathway might be evaluated as immunotherapies in humans.